2005
DOI: 10.1021/om049022a
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Organometallic Ruthenium(II) and Osmium(II) Complexes to an Oligonucleotide:  A Combined Mass Spectrometric and Theoretical Study

Abstract: A series of ruthenium(II) and osmium(II) p-cymene dichloride complexes with either a pta (1,3,5-triaza-7-phosphatricyclo[3.3.1.1]decane) or [pta-Me]Cl ligand which exhibit anticancer activity have been prepared and characterized by 1 H and 31 P NMR spectroscopy and mass spectrometry. Three of the complexes, viz. [Os(η 6 -p-cymene)Cl 2 (pta)] and [M(η 6 -pcymene)Cl 2 (pta-Me)]Cl (M ) Ru, Os), have also been characterized by single-crystal X-ray diffraction. The pta complexes are selective anticancer agents, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
190
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 211 publications
(205 citation statements)
references
References 46 publications
(62 reference statements)
12
190
0
3
Order By: Relevance
“…[84][85][86] In the cases of angiotensin and bombesin, the fragmentation was performed using CID, while additional data were obtained using ECD. The results showed that the primary binding sites of such complexes were methionine and histidine residues, with phenylalanine being a potential secondary site The potential interaction of Ru(II), [87][88][89][90] Ru(III) [90,91] and dinuclear Ru(II) [92] anticancer agents towards oligonucleotides was also studied by ESI-MS. For instance, RAPTA derivatives as well as their osmium analogues were investigated for their reactivity towards a 14-mer single stranded oligonucleotide. [89] The results showed that while RAPTA-C gives rise to Ru-oligonucleotide mono-adducts following detachment of the arene, the osmium analogue forms both mono-and bis-adducts with maintenance of the arene moiety.…”
Section: Ruthenium Complexesmentioning
confidence: 99%
“…[84][85][86] In the cases of angiotensin and bombesin, the fragmentation was performed using CID, while additional data were obtained using ECD. The results showed that the primary binding sites of such complexes were methionine and histidine residues, with phenylalanine being a potential secondary site The potential interaction of Ru(II), [87][88][89][90] Ru(III) [90,91] and dinuclear Ru(II) [92] anticancer agents towards oligonucleotides was also studied by ESI-MS. For instance, RAPTA derivatives as well as their osmium analogues were investigated for their reactivity towards a 14-mer single stranded oligonucleotide. [89] The results showed that while RAPTA-C gives rise to Ru-oligonucleotide mono-adducts following detachment of the arene, the osmium analogue forms both mono-and bis-adducts with maintenance of the arene moiety.…”
Section: Ruthenium Complexesmentioning
confidence: 99%
“…We have been interested for some years in the applications of arene and cyclopentadienyl Ru complexes bearing the water-soluble monodentate phosphine PTA in selective hydrogenation reactions, 9,13 and in medicinal applications, 11,12,14 -17 and recently extended these studies to other transition metals 18,19 and ligand modifications to observe their implications in catalysis; 20 -23 the various aspects of PTA chemistry have been recently reviewed. 24 Under hydrogenation conditions, (pentamethyl) cyclopentadienyl Ru PTA complexes usually showed higher stability than the corresponding arene complexes, thus they are reasonable candidates as catalysts for CO 2 hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the complexes formed between cisplatin/A15, HAuCl4/A15, Hg 2+ /T15 and Ag + /C15, only the cisplatin adduct is stable under the denaturing gel electrophoresis condition. Each Pt-nucleobase bond gives a positive charge and thus makes DNA a zwitterionic 15 polymer. This allows ultrafast adsorption of DNA by graphene oxide (GO) and the adsorbed complex is highly stable.…”
mentioning
confidence: 99%
“…In the first two cases, an A15 DNA (e.g. a 15-mer DNA with all adenine bases) is respectively reacted with 15 cisplatin and HAuCl4. Pt 2+ and Au 3+ have the same electronic structure and are right next to each other the periodic table, forming a good pair for comparison.…”
mentioning
confidence: 99%
See 1 more Smart Citation